Story of the ALS-FTD continuum retold: rather two distinct entities - Lulé, Dorothée; Aho-Özhan, Helena E. A.; Vázquez, Cynthia; Weiland, Ulrike; Weishaupt, Jochen H.; Otto, Markus; Straub, Sarah; Semler, Elisa; Uttner, Ingo; Ludolph, Albert C. (Journal of neurology, neurosurgery, and psychiatry, 2019)
Objective To determine the evolution and profile of cognitive and behavioural deficits in amyotrophic lateral sclerosis (ALS) and behavioural variant frontotemporal dementia (bvFTD) to disentangle the development of FTD in ALS and vice versa. Methods In a prospective design, cognitive and behavioural profiles of 762 patients with motor predominant ALS (flail arm/leg syndrome, primary lateral sclerosis, pseudobulbar palsy, ALS) and behavioural predominant FTD (bvFTD, ALS-FTD) were determined and caregivers of patients with ALS were asked on the evolution of behavioural symptoms. Data were compared with 49 healthy controls. Cognition was measured with the Edinburgh Cognitive and Behavioral ALS Screen. Results Evolution and features of cognitive profile of patients with motor predominant ALS were distinctly different from patients with behavioural FTD with regard to number and degree of affected cognitive domains. Also, in ALS mostly minus symptoms evolved after physical symptom onset whereas in ALS-FTD plus and minus symptoms were reported with an onset before physical degradation. Conclusion Evolution of cognitive and behavioural profile in patients with motor predominant ALS is distinctly different from those psychocognitive findings in patients with behavioural variant dementia. This may support the hypothesis that (possibly genetic) triggers decide in the preclinical phase on either motor or psychocognitive phenotypes.
Zuerst online veröffentlicht: 26. September 2018
Gesehen am 08.07.2021